Paluparan han Borongan redeveloping Borongan Airport into a tourism-generative Hybrid Estate as a Gateway to Eastern SamarPaluparan han Borongan: Redeveloping Borongan Airport into a Tourism-generative hybrid estate as a gateway to Eastern Samar - Abing, Jean Kelly
The Paluparan han Borongan (Airport of Borongan) serves as the sole commercial airport in the province of Eastern Samar after recently resuming biweekly operations succeeding years of hiatus. Accessibility is vital in the success of the tourism campaigns of a locality, especially for Eastern Samar, which belongs to a primarily agricultural region currently ranked as the third lowest in terms of GDP per capita in the Philippines in 2023. While the agriculture, forestry, and fishing industries trail last in GDP growth rates at 0.5%, the accommodation and food service industries lead at 32.1%, presenting an opportunity for the province to further bolster their economic profile by incorporating these industries into the development plan through tourism. Borongan Airport in Punta Maria poses development potential due to its central location in the province capital and its proximity to the top tourist attraction of the city. At its current capacity, the airport’s facilities may not be able to accommodate the impending influx of passengers once the province’s tourism campaign is underway, as it is envisioned to facilitate the majority of domestic flights for tourist and local passengers inbound for Eastern Samar. The airport is to be developed into a hybrid tourism estate with transportation infrastructure adjoined by harmonious commercial, cultural, and recreational facilities. The estate is to address the inherent climatic vulnerabilities through adaptive spatial configurations, renewable energy, and vernacular materials, while also embodying the local essence of Borongan through cultural imagery and materials.